2014
DOI: 10.1080/11263504.2014.990536
|View full text |Cite
|
Sign up to set email alerts
|

Natural habitats of typical plants growing on ruins of Roman archaeological sites (Rome, Italy)

Abstract: In this study, we support the hypothesis that wall plant species come mainly from rocky habitats, taking into account that ancient walls show similar characteristics to rocks. The occurrence of wall species in natural habitats was investigated. The main literature concerning wall and natural vegetation of central-southern Italy was viewed. Vegetation synoptic tables were analysed through statistical procedures for comparing occurrence and behaviour of wall species in ruderal habitats as archaeological sites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Previous studies reported that horizontal surfaces, which provide better growing conditions, usually host a higher plant cover compared to vertical walls [38] [39]. In our case, more species were detected on vertical than on horizontal surfaces in agreement with Motti et al 2020 [40].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reported that horizontal surfaces, which provide better growing conditions, usually host a higher plant cover compared to vertical walls [38] [39]. In our case, more species were detected on vertical than on horizontal surfaces in agreement with Motti et al 2020 [40].…”
Section: Discussionsupporting
confidence: 91%
“…Archaeological and historical sites are often integrated in urban environments where stone monuments and vegetation (from trees to mosses), and microorganisms, interact (Cicinelli et al, 2018). Indeed, depending on composition, exposure, and porosity of the substrate, plant and microflora communities can grow on different habitats, both vertical and horizontal, such as walls, ruins, rocky surfaces, sculptures, and stone and marble artifacts (Ceschin et al, 2016).…”
Section: Damages To Urban Artifacts and Monumentsmentioning
confidence: 99%
“…Owing to their high degree of environmental heterogeneity and to different management practices, these sites support a rich diversity of wild, mainly native, plants (Ceschin et al 2016). Ancient walls are the most common host environment of the flora in these sites.…”
Section: Study Areamentioning
confidence: 99%
“…A number of studies have been conducted on the impact of other taxonomic groups, such as fungi, lichens and bryophytes, on the biodeterioration of stone monuments (Salvadori and Casanova 2016;Warscheid and Braams 2000) and advances have been made in our knowledge of the plant cover of archaeological areas (Ceschin et al 2016) particularly of the most noxious native species, such as ivy (Hedera helix L., Bartoli et al 2017). However, a gap in research on non-native flora growing in heritage sites remains.…”
Section: Introductionmentioning
confidence: 99%